Implikasi Prinsip Transfer of Undertaking Protection of Employment (TUPE) Terhadap Hak-Hak Pekerja Berstatus Perjanjian Kerja Waktu Tertentu (PKWT) - Imam Buchari (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
The purpose of this study was to determine the Principle of Transfer of Undertaking Protection of Employment (TUPE) in Indonesia’s outsourcing companies, the concept of a Specific Time Work Agreement (PKWT) in outsourcing companies and to investigate the implementation of TUPE principles on the rights of outsourcing workers with the Agreement status. In order to protect the rights of outsourced workers with the agreement status, the service provider company is obliged to include clauses on guarantees for continuity of work, guarantees for the fulfillment of workers' rights in accordance with applicable laws and regulations and guarantees for calculating the working period in the event of a change in the service provider company to set wages.